Automatic Japanese license plate recognition at car park entrance - Hong, Yun (2014)
This report summarizes work done by author for final year project and describes work procedure in details. The project title is Automatic Japanese License Plate Recognition at Car Park Entrance. Due to time constrain and source limitation, the focus of this project is set to be recognizing Japanese characters correctly.